From ambition to substance use tendency: the mediating role of significance quest - Şahin, Ekrem Sedat (Frontiers in Psychology, 2025)
In this study, the aim was to determine the mediating effect of the quest for significance on the relationship between ambition and substance use tendency in emerging adults. Data were collected from emerging adults studying at various universities in Turkey through both face-to-face and online processes. A total of 506 emerging adults (X¯age = 21.62) participated in the study. The Ambition Scale, Significance Quest Scale, Substance Initiation Tendency Scale, and a demographic form were used to gather data. Structural equation modeling was employed to analyze the data. The results revealed a positive and significant relationship between ambition and the quest for significance, as well as between the quest for significance and substance use tendency in emerging adults. Furthermore, the quest for significance was found to mediate the relationship between ambition and substance use tendency in this population. Suggestions were provided based on the findings of the study.